2009
DOI: 10.1063/1.3136862
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave mediated exciton dissociation in a ZnCdSe/LiNbO3 hybrid

Abstract: Independent dynamic acousto-mechanical and electrostatic control of individual quantum dots in a LiNbO 3 -GaAs hybrid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…In a piezoelectric material the periodic mechanical deformation is accompanied by electric fields which induce currents dissipating energy. Whilst for high SAW intensities (P SAW > 20 dBm) a modulation of the conduction and valence band edges leads to a dissociation of optically generated excitons, thus quenching the photoluminescence [8], in the regime of low powers P SAW = −20 dBm, used in all presented measurements, the photoluminescence signal of the QW is not yet altered or quenched. The SAW propagation hence acts only as a weak perturbation of the system and a measurement of the SAW transmission in this power range provides a non-invasive probe of the conductivity.…”
Section: B Experimental Setupmentioning
confidence: 92%
See 2 more Smart Citations
“…In a piezoelectric material the periodic mechanical deformation is accompanied by electric fields which induce currents dissipating energy. Whilst for high SAW intensities (P SAW > 20 dBm) a modulation of the conduction and valence band edges leads to a dissociation of optically generated excitons, thus quenching the photoluminescence [8], in the regime of low powers P SAW = −20 dBm, used in all presented measurements, the photoluminescence signal of the QW is not yet altered or quenched. The SAW propagation hence acts only as a weak perturbation of the system and a measurement of the SAW transmission in this power range provides a non-invasive probe of the conductivity.…”
Section: B Experimental Setupmentioning
confidence: 92%
“…Due to the increased coupling coefficient, K eff , of LiNbO 3 compared to Zn(Cd)Se this hybrid sample layout efficiently gives access to higher piezoelectric fields in the semiconductor material which e.g. was used to study SAW mediated exciton dissociation [8]. A microscope image of one part of the sample is shown in the inset to Surface acoustic waves are attenuated in the presence of free charge carriers close to the sample surface.…”
Section: B Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…II-VI epitaxial layers deposited on an MgS layer 5-10 nm thick can be easily detached from the substrate with little change in the strain and PL efficiency of the layers and we have shown that structures containing both an MgS release layer and Zn 0.2 Mg 0.8 S 0.64 Se 0.36 , barrier layers can be fabricated [28]. Using this method II-VI structures can be transferred to other substrates such as glass, dielectric Bragg mirrors [29] or lithium niobate SAW structures [30,31].…”
Section: Development and Applications Of Metastable Mgs And Mgsrich Amentioning
confidence: 92%
“…3 ELO layers have been successfully transferred to alternative substrates such as glass, laser diodes, 4 distributed Bragg reflectors (DBRs), 5 and LiNbO 3 . 6 While fabricating these and other devices, it was observed that the adhesion of the lifted layer varied according to the alternative substrate material chosen. Determination of the adhesion energy of II-VI materials on different surfaces could provide better understanding of how to handle and process ELO films.…”
Section: Introductionmentioning
confidence: 99%